2014
DOI: 10.1088/0268-1242/29/4/045018
|View full text |Cite
|
Sign up to set email alerts
|

Hot-phonon lifetime in Al0.23Ga0.77N/GaN channels

Abstract: Hot-phonon effects on hot-electron noise and transport are investigated in nominally undoped two-dimensional Al 0.23 Ga 0.77 N/GaN channel with electron density of 7.4 × 10 12 cm −2 . The electrons are subjected to electric field applied in the channel plane. The dependence of noise temperature on supplied electric power yields hot-phonon lifetime of (370 ± 100) fs at low levels of power (<1 nW/electron). Monte Carlo simulation of hot-electron drift velocity with the same lifetime value as a model parameter co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The sheet carrier concentration and electron mobility obtained by Hall measurements were 7.3 Â 10 12 cm À2 and 1150 cm 2 /V s, respectively. 12 Prior to metal deposition, the samples were cleaned and a resist mask was applied by optical lithography. Subsequently, different metal stacks were deposited by electron beam evaporation (Table I).…”
mentioning
confidence: 99%
“…The sheet carrier concentration and electron mobility obtained by Hall measurements were 7.3 Â 10 12 cm À2 and 1150 cm 2 /V s, respectively. 12 Prior to metal deposition, the samples were cleaned and a resist mask was applied by optical lithography. Subsequently, different metal stacks were deposited by electron beam evaporation (Table I).…”
mentioning
confidence: 99%
“…A summary of all these heterostructures is given in Table II. whether self-heating has an influence on current-electric field characteristics at high electric fields, we tried to calculate the hot-phonon lifetime in our samples. Because, the hotphonon effects are weaker when the lifetime is shorter and Liberis et al [33] and Barker et al [34] have shown that hotphonon effects may not be very serious and the suggested hot phonon lifetime is less than 0.3 ps. In our samples, it is estimated that the hot-phonon lifetime in our samples changes between 0.01 and 0.13 ps at high fields using a simple expression suggested by several studies to calculate hot phonon lifetime [35], [36].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 24. Hot-phonon lifetime in 2DEG channels located in ZnO/Mg 0.38 Zn 0.62 O/ZnO structure (green star, present project) together with the data for 2DEG channels confined in GaN (black bullets [7], blue star [39], red triangle [41]), InGaAs (red circles [7]) and InGaN (blue square [40]). Solid curves illustrate Eq.…”
Section: Ultrafast Decay Of Hot Phonons In 2deg Channelsmentioning
confidence: 88%